Surveillance of rhinovirus diversity among a university community identifies multiple types from all three species including an unassigned rhinovirus A genotype. Issue 1 (28th September 2022) - Faleye, Temitope O. C.; Elyaderani, Amir; Skidmore, Peter; Adhikari, Sangeet; Smith, Abriana; Kaiser, Nicole; Sandrolini, Helen; Finnerty, Sarah; Halden, Rolf U.; Varsani, Arvind; Scotch, Matthew
Abstract: We determine the presence and diversity of rhinoviruses in nasopharyngeal swab samples from 248 individuals who presented with influenza‐like illness (ILI) at a university clinic in the Southwest United States between October 1, 2020 and March 31, 2021. We identify at least 13 rhinovirus genotypes (A11, A22, A23, A25, A67, A101, B6, B79, C1, C17, C36, and C56, as well a new genotype [AZ88**]) and 16 variants that contributed to the burden of ILI in the community. We also describe the complete capsid protein gene of a member (AZ88**) of an unassigned rhinovirus A genotype.